Pengaruh Kualitas Layanan, Harga dan Gaya Hidup Terhadap Keputusan Pembelian Tiket Kereta Api Melalui KAI Access (Studi Kasus Pada Mahasiswa Di Kota Malang) - Rizma Akbarani; Nur Hidayati; Muhammad Khoirul Anwarodin Broto Suharto (UNIVERSITAS ISLAM MALANG, 2023)
Abstract The purpose of this study was to determine and analyze the effect of service quality, price and lifestyle on the decision to purchase train tickets through KAI Access. Sampling was carried out on students in Malang City using the Malhotra formula so that a sample of 85 respondents was obtained. This research method uses multiple linear regression analysis with the SPSS analysis tool. This study shows that service quality, price and lifestyle have a simultaneous effect on purchasing decisions. Tests carried out with partial tests, all variables have a significant positive effect on the dependent variable Keywords: Quality Of Service, Price, Lifestyle Purchase Decision